Switched Inductor Quasi-Z-Source Based Back-to-Back Converter for Variable Speed Wind Turbines with PMSG - Bisenieks, L.; Vinnikov, D.; Ott, S. (Elektronika ir Elektrotechnika, 2011)
This paper presents a new converter topology for interfacing a permanent magnet synchronous generator based variable speed wind turbine with a residential power network. Analysis of the converter topologies studied earlier shows that they are not well suited for PMSG with low output voltage. PMSG characteristics are discussed in order to formulate requirements for a power converter. A new topology of an interfacing converter is analyzed and simulation results of a lossless model are presented. Simulation results of the proposed converter prove that its utilization in wind power applications is beneficial. The results of performance tests demonstrate the SL qZSI ability to ensure the required sinusoidal output voltage at all operation modes of PMSG-based WSVT. Ill. 15, bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.698